Functional beverage based on aguamiel pasteurized by ultrasound and microwaves with antihypertensive properties - Lucia Perales‐Serna; Dora Elisa Cruz‐Casas; Adriana C. Flores‐Gallegos; Anilú Rubio‐Ríos; Juan Alberto Ascacio‐Valdes; Aidé Sáenz‐Galindo; Raúl Rodríguez‐Herrera (eFood, 2024)
Abstract Currently, microwaves, ultrasound, and ultrasound‐microwaves are technologies with several applications, one of which is their use as a method of pasteurization. So far, these techniques have not been used for the pasteurization of a functional aguamiel beverage. This beverage was pasteurized and enriched with probiotic LAB to generate an antihypertensive effect. The physicochemical characteristics (pH, total soluble solids, and color) of the aguamiel beverage were evaluated. Microbiological analysis of the product was also carried out. The probiotic LAB were added to the beverage with the selected pasteurization technique. The growth of LAB in the aguamiel beverage and the prebiotic effects that this product as well as the antihypertensive activity of the beverage were evaluated. It was shown that there is no significant effect of the techniques used on the physicochemical characteristics of the product. However, the storage time may be affected. Compared to traditional pasteurization, microwave, ultrasound, and ultrasound‐microwave techniques were found to reduce the concentration of some pathogenic microorganisms. The microwave technique was selected as the most effective for pasteurization. The probiotic LAB were able to grow in the pasteurized aguamiel beverage and produce an antihypertensive effect. In summary, a functional microwavable pasteurized aguamiel beverage with antihypertensive activity was produced.